An Energy Efficient and Trust Aware Framework for Secure Routing in LEACH for Wireless Sensor Networks - Miglani, Arzoo (My University, 2015)
Wireless Sensor Network (WSN) is an advanced technology and has been used widely in many applications such as health monitoring, environment monitoring, military purpose etc. Nature of this network is that they are often placed in an open environment and are susceptible to various attacks. Traditional cryptography methods are not supportable in WSNs as they have high energy and resource constraints. Trust management has been proved to be an effective measure to enhance security as well as to handle threats for WSNs. Trust can be defined as level of reliableness in a node. Low Energy Adaptive Clustering (LEACH) is a cluster based routing protocol for WSN which is superior to direct communication protocol and known for its minimum transmission energy. However, LEACH itself has some limitations related to security. In this thesis, an energy efficient and trust aware framework for secure routing in LEACH (EETA-LEACH), has been proposed that improves LEACH protocol by introducing trust to provide secure routing, while maintaining originality of LEACH protocol. This approach is a combination of trust-based routing module and trust management module that works together to select trusted Cluster Head (CH). The simulation results demonstrate that proposed scheme is better in terms of network lifetime and Packet Delivery Ratio (PDR). It is verified that malicious nodes will not be selected as CH and trust value of a malicious node decreases with time.
M.E. (Information Security, CSED)
Keywords: WSNs; Trust management; LEACH; Attacks in sensor network; Cluster based wireless sensor network; CSED